New One CGIAR initiative to transform livestock productivity, nutrition and gender inclusion in northwest Vietnam - Chi Nguyen (International Livestock Research Institute, 2022)
Co-creation, with stakeholders, of the SAPLING vision and theory of change for the pig, beef cattle and chicken value chains in Vietnam.